Multispectral Phloem-Mobile Probes: Properties and Applications. Issue 4 (4th February 2015) - Knoblauch, Michael; Vendrell, Marc; de Leau, Erica; Paterlini, Andrea; Knox, Kirsten; Ross-Elliot, Tim; Reinders, Anke; Brockman, Stephen A.; Ward, John; Oparka, Karl
Abstract : New fluorescent probes allow the study of phloem transport in Arabidopsis. Abstract: Using Arabidopsis ( Arabidopsis thaliana ) seedlings, we identified a range of small fluorescent probes that entered the translocation stream and were unloaded at the root tip. These probes had absorbance/emission maxima ranging from 367/454 to 546/576 nm and represent a versatile toolbox for studying phloem transport. Of the probes that we tested, naturally occurring fluorescent coumarin glucosides (esculin and fraxin) were phloem loaded and transported in oocytes by the sucrose transporter, AtSUC2. Arabidopsis plants in which AtSUC2 was replaced with barley ( Hordeum vulgare ) sucrose transporter (HvSUT1), which does not transport esculin in oocytes, failed to load esculin into the phloem. In wild-type plants, the fluorescence of esculin decayed to background levels about 2 h after phloem unloading, making it a suitable tracer for pulse-labeling studies of phloem transport. We identified additional probes, such as carboxytetraethylrhodamine, a red fluorescent probe that, unlike esculin, was stable for several hours after phloem unloading and could be used to study phloem transport in Arabidopsis lines expressing green fluorescent protein.